Optimisation study of catalytic cracking of refined rubber seed oil for biogasoline production using response surface methodology - Singh, H.K.G. (Springer International Publishing, 2019)
The continuous dependence on the non-renewable fossil fuel could result in diminishing petroleum reserves and environmental degradation in times to come. Early steps to avert this is by developing an alternative fuel of good quality and ecofriendly that is compatible with the existing car engines. Hence, this study evaluates the efficiency of Cu/ZSM-5 catalyst in promoting gasoline range hydrocarbons for the catalytic cracking of refined rubber seed oil. The parametric conditions such as temperature (350-500 °C) and weight hour space velocity, WHSV (1-4 h-1) were optimised using Response Surface Methodology Design (RSM) in a fixed-bed reactor at atmospheric condition. The aim of the optimisation study was to achieve a balance between productivity, fuel quality and environment security. Therefore, the optimal operating conditions were achieved at temperature of 440 °C and WHSV of 1.7 h-1 producing paraffin, isoparaffin and aromatics distribution of 6.42, 1.67 and 78.1, respectively, with 91.7 of conversion and 49.67 of gasoline selectivity. © Springer Nature Switzerland AG 2019.